A semaphorin-plexin-Rasal1 signaling pathway inhibits gastrin expression and protects against peptic ulcers - Xu, Rui; Höß, Carsten; Swiercz, Jakub M.; Brandt, Dominique T.; Lutz, Veronika; Petersen, Natalia; Li, Rui; Zhao, Dandan; Oleksy, Arkadiusz; Creigh-Pulatmen, Tilbe; Trokter, Martina; Fedorova, Marina; et al. (Science translational medicine, 2022)
Peptic ulcer disease is a frequent clinical problem with potentially serious complications such as bleeding or perforation. A decisive factor in the pathogenesis of peptic ulcers is gastric acid, the secretion of which is controlled by the hormone gastrin released from gastric G cells. However, the molecular mechanisms regulating gastrin plasma concentrations are poorly understood. Here, we identified a semaphorin-plexin signaling pathway that operates in gastric G cells to inhibit gastrin expression on a transcriptional level, thereby limiting food-stimulated gastrin release and gastric acid secretion. Using a systematic siRNA screening approach combined with biochemical, cell biology, and in vivo mouse experiments, we found that the RasGAP protein Rasal1 is a central mediator of plexin signal transduction, which suppresses gastrin expression through inactivation of the small GTPase R-Ras. Moreover, we show that Rasal1 is pathophysiologically relevant for the pathogenesis of peptic ulcers induced by nonsteroidal anti-inflammatory drugs (NSAIDs), a main risk factor of peptic ulcers in humans. Last, we show that application of recombinant semaphorin 4D alleviates peptic ulcer disease in mice in vivo, demonstrating that this signaling pathway can be harnessed pharmacologically. This study unravels a mode of G cell regulation that is functionally important in gastric homeostasis and disease.